Struktur Modal berdasarkan Pecking Order Theory pada Perusahaan Makanan dan Minuman di Indonesia - pandu adi cakranegara; Debby Danilla Wati (President University Press, 2020)
Pecking Order theory states that management will prioritize its own capital before using debt. If it is forced to need additional funds then management will choose to owe rather than issue equity. This study examines the management behavior in the food and beverage industry in Indonesia. The food and beverage industry in Indonesia today is the industry with the highest growth in Indonesia. This means that companies need funding to be able to capture this momentum. The method used is a quantitative method using multiple regression analysis. The samples taken are all food and beverage companies listed on the Indonesian Stock Exchange. From the findings of management authors in food and beverage companies tend to use debt and equity issuance and do not use cash flow generated from business. One of the reasons for this is that the company uses all the cash generated from the operating proceeds to invest directly in the company's internal projects to increase growth.